DIGITAL TRANSFORMATION STUDY IN SMES : SYSTEMATIC LITERATURE REVIEW (SLR) - Setiawan, Bagus; Sudarmiatin; Eko Soetjipto , Budi (Nusantara Economics and Entrepreneurships Journals, 2023)
The development of digital technology has affected all aspects of life including SMEs. SMEs in the digital era have developed well, but the reality of digital transformation does need a process of adaptation and not all business fields are able to adjust to digitalization. The purpose of this study is to map influential concepts related to digital transformation in Small and Medium Enterprises (SMEs) through conducting a systematic literature review and finding a better understanding of current knowledge. The systematic process has resulted in the final count of 10 journals from Emerald Insight. The method used is PRISMA, which is further studied and the results analyzed qualitatively. The results of a review in 10 (ten) journals by reviewing literature from the last month, showed that the majority gave a good response in the digital transformation process and some in addition mentioned enough or less. This means that there are differences in process improvement and capabilities in terms of digital development and traditional production.